Renal Calcifications in Symptomatic Primary Hyperparathyroidism With Massive Hypercalcemia in 47-Year-Old-Man: A Case Report With Literature Review - Muhammad Akbar; Timotius Timotius; Diana Novitasari; Johansen Johansen; Steven Tanuwidjaja (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Primary hyperparathyroidism (PHPT) is a disorder of the parathyroid glands where there is excessive production of PTH from one or more parathyroid glands. Eventually, it causes an increase in calcium levels in the blood or hypercalcemia. We report the case of a 47-year-old man with major complaints of right waist pain. Pain is felt up to the thigh and worsens when walking or doing an activity. On local examination of the neck area, there was no visible mass the inspection, and on palpation, there was no lump or mass in the neck area. There was tenderness in the right and left costovertebral angle (CVA) on abdominal examination. On laboratory examination, PTH levels were 455.8 pg/Ml. Calcium levels were 13.5 mg/dL, creatinine was 2.6 mg/dL, urea was 64.9 mg/dL. On abdominal ultrasound, multiple hyperechoic lesions were found on the right and left kidneys measuring 6 – 12 mm with the impression of nephrolithiasis and on urological CT scan without contrast, multiple calcifications in both kidneys were found. The patient underwent percutaneous nephrolithotomy (PCNL) to remove kidney stones.